국내 환자안전사고 관련 요인 분석 - 김남이(Kim, Nam Yi) (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2020)
목적: 본 연구의 목적은 한국의 '2018년 환자안전보고 데이터'를 분석하여 환자안전사고와 관련된 요인을 분석하고, 환자안전사고 예방 및 중재 방안을 마련하는데 있다. 방법: 2019년에 발표된 ‘2018년 환자안전보고 데이터’에 대해 분석하였다. 2018년에 9,250건의 환자안전사고가 보고되었으며, 500병상 이상 병원의 데이터 3,757건을 분석하였다. SPSS 25.0을 이용하여 교차분석 및 다항 로지스틱 회귀분석을 하였다. 결과: 적신호사건에 영향을 미치는 요인은 없었다. 위해사건의 경우 연령, 입원실, 치료실, 간호사의 낮 근무 시간, 낙상, 수혈 및 약물이 주요 요인이었다. 결론: 환자안전사고를 예방하기 위해 환자의 연령이 많은 경우 언어적, 비언어적 의사소통에 귀를 기울이고, 질병의 복합성을 이해하고 이에 대한 지식을 갖추어야 한다. 또한 간호사의 초과근무를 줄이도록 하는 근무환경 개선이 필요하며, 환자 모니터링 시스템과 낙상예방활동, 환자안전규정과 절차를 전산화하여 인적 오류를 줄일 수 있는 방안을 모색해야 할 것이다. Purpose: The purpose of this study was to analyze factors related to patient safety incidents by analyzing '2018 patient safety report data' for Korea, and to prepare a plan for preventing patient safety incidents. Methods: Analysis was done for 2018 patient safety report data’published in 2019. In 2018, 9,250 patient safety incidents were reported, and for this study data (3,757) from hospitals with more than 500 beds were analyzed. SPSS 25.0 was used for the crosstabulation analysis and multinominal logistic regression. Results: There were no factors affecting the sentinel event. The main factors of adverse events were age, patient room, treatment room, day duty of nurses, falls, transfusions, and medication. Conclusion: In order to prevent patient safety incidents, elderly patients should receive verbal and nonverbal communication that will help them understand the complexity of the disease. Finding ways to reduce nurse overtime and reduce human error by computerizing patient monitoring systems, fall prevention activities, and patient safety regulations and procedures are necessary. KCI Citation Count: 1